Genetic improvement of variety pattern chromatic Half Black- Blue or Diamond of ornamental fish Guppy (Poecilia reticulata; Peters, 1859) through mass selection - Scotto Espinoza, Carlos (2011)
This article provides a standard computerized digitized based on the number of pixels. They found eight characteristic blue color tones in both the body and dorsal fin to be used in the potential for mass selection breeding color pattern of the commercial variety or Half Black-Blue Diamond ornamental fish Guppy (Poecilia reticulata). Ten pairs of sires selected with an average of eighty F1 offspring per couple (Total = 734), were randomly selected twelve male animals more attractive for its beauty subjective color, divided into two groups, one blue and one to find a light blue color digital mathematical pattern by the number of pixels.